Overexpression and secretion of AgaA7 from Pseudoalteromonas hodoensis sp. nov in Bacillus subtilis for the depolymerization of agarose - Ramos, Kristine Rose M. (Animo Repository, 2016)
Interest in agar or agarose-based pharmaceutical products has driven the search for potent agarolytic enzymes. An extracellular -agarase (AgaA7) recently isolated from Pseudoalteromonas hodoensis sp. nov was expressed in Bacillus subtilis, which was chosen due to its capability to overproduce and secrete functional enzymes. Phenotypic analysis showed that the engineered B. subtilis secreted a functional AgaA7 when fused with the aprE signal peptide (SP) at the amino-terminus. The maximum agarolytic activity was observed during the late logarithmic phase. To further improve the secretion of AgaA7, an expression library of AgaA7 fused to different naturally occurring B. subtilis SPs was created. The amount of AgaA7 secreted by the clones was compared through activity assay, immuno-blot, and purification via affinity chromatography. Although the aprE SP can readily facilitate the secretion of AgaA7, other SPs such as yqgA, pel, and lipA were relatively more efficient. Among these SPs, lipA was the most efficient in improving the secretion of AgaA7.The use of B. subtilis as host for the expression and secretion of agarolytic and other hydrolytic enzymes can be a useful tool in the field of white biotechnology.